Fasudil Improves Motor Functions Against Rotenone-Induced Neurotoxicity in Rats - Kumar, Abhishek (Asian Journal of Pharmaceutics (AJP), 2025)
Parkinson’s disease (PD), the second most frequent neurodegenerative disease, involves the progressive loss of dopaminergic neurons in the substantia Nigra, resulting in motor dysfunction. Recently, Rho- associated protein kinase (ROCK) has been associated with Parkinson’s pathology. Fasudil (FSD), a ROCK inhibitor, offers neuroprotection; however, its precise mechanism remains to be explored in the rotenone (ROT)- exposed animal model. Objectives: This study aimed to evaluate the therapeutic effectiveness of FSD in mitigating ROT -induced neurotoxicity by attenuating oxidative stress (OS) in a Parkinsonian rat model. Materials and Methods: Wistar rats were exposed to ROT (2.5 mg/kg; i.p.,) for 28 days to induce Parkinson’s-like symptoms. Subsequently, FSD (10 mg/kg; p.o.) was administered daily for 28 days in the treatment group. The behavioral and biochemical assessments were conducted to evaluate motor functions, OS, dopamine (DA) levels, and mitochondrial functions. Results: Administration of ROT caused increased motor dysfunction and OS, along with a reduction in dopaminergic content. FSD treatment reversed the motor and biochemical impairments caused by ROT by restoring DA levels, enhancing enzymatic antioxidant activity, and reducing lipid peroxidation, thereby protecting dopaminergic neurons. Conclusion: The present study demonstrated that FSD has a neuroprotective effect in ROT -induced neurotoxicity, mediated by inhibiting the ROCK pathway, which results in the restoration of antioxidant and DA levels.